Efficacy of a combination of HBV RNA and HBeAg in predicting HBeAg seroconversion in patients treated with entecavir for 144 weeks. (October 2020) - Wang, Xiaomei; Wang, Zhongfeng; Chi, Xiumei; Wu, Ruihong; Jin, Qinglong; Xu, Hongqin; Gao, Xiuzhu; Yu, Lei; Chen, Yuping; Shang, Jia; Liu, Longgen; Zhang, Shuqin; et al.
Highlights: The dynamic changes of HBV RNA, the correlation of HBV RNA with cccDNA, and the performance of HBV RNA combined with known HBV markers in predicting HBeAg seroconversion during entecavir treatment were analyzed in the same cohort. The serum HBV RNA was positively correlated with cccDNA among all patients at baseline, but the correlation disappeared in the HBeAg seroconversion group at week 48. The combination of HBV RNA and HBeAg at week 24 was a powerful predictor of HBeAg seroconversion in HBeAg positive patients with 144-week entecavir treatment. Abstract: Background: In some previous studies, serum hepatitis B virus RNA (HBV RNA) was proposed as an HBV viral marker during therapy. However, the dynamic change of HBV RNA, the correlation of HBV RNA with cccDNA, and the combination of HBV RNA with known HBV markers in predicting entecavir (ETV) treatment outcome in the same cohort are rarely reported. Methods: A total of 111 HBeAg-positive patients were enrolled in our study. The dynamic changes of serum HBV RNA and the correlation of HBV RNA with other HBV markers were investigated in the early treatment period of 144-week ETV treatment. Intrahepatic cccDNA was detected at baseline and week 48. Receiver operating characteristic analyses were used to identify HBV RNA levels associated with HBeAg seroconversion. Results: The serum HBV RNA levels decreased more rapidly in patients with HBeAg seroconversion than those without HBeAg seroconversion. The levels of HBV RNA decreased slower compared with the serum HBV DNA, irrespective of whether the patients achieved HBeAg seroconversion or not. Although the serum HBV RNA was positively correlated with cccDNA at baseline among all patients, no significant correlation was observed in the patients with HBeAg seroconversion at week 48 ( r = 0.094, P = 0.588). The area under the receiver operating characteristic (AUROC) of HBV RNA and HBeAg at week 24 was 0.754 and 0.800, respectively. The AUROC of the HBV RNA and HBeAg combination had a higher value (AUROC = 0.821). Conclusions: The level of HBV RNA at week 24 was a powerful predictor of HBeAg seroconversion in HBeAg-positive patients after 144-week ETV treatment, while the combination of HBV RNA and HBeAg was superior to HBV RNA alone in predicting HBeAg seroconversion.